2015
DOI: 10.1186/s12960-015-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

Applying a typology of health worker migration to non-EU migrant doctors in Ireland

Abstract: BackgroundResearch on health worker migration in the Irish context has categorized migrant health workers by country or region of training (for example, non-EU nurses or doctors) or recruitment mechanism (for example, actively recruited nurses). This paper applies a new typology of health worker migrants – livelihood, career-oriented, backpacker, commuter, undocumented and returner migrants (European Observatory on Health Systems and Policies and WHO, vol. 2:129-152, 2014) – to the experiences of non-EU migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…However, progress has been slow in Ireland, where the negative impact of the 2008 financial crisis and the associated 30% pay reduction continue to have effect. Many of the recommendations made by the MacCraith report, especially around retention, have not been successful 33 34. Poorer working conditions, unequal remuneration and type of contract were found to adversely affect BO levels among consultants in Ireland, where a two tier consultant contract exists 22.…”
Section: Discussionmentioning
confidence: 99%
“…However, progress has been slow in Ireland, where the negative impact of the 2008 financial crisis and the associated 30% pay reduction continue to have effect. Many of the recommendations made by the MacCraith report, especially around retention, have not been successful 33 34. Poorer working conditions, unequal remuneration and type of contract were found to adversely affect BO levels among consultants in Ireland, where a two tier consultant contract exists 22.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important that doctors who are planning to migrate are aware of the training and career obstacles, as well as the opportunities, likely to be faced in the destination country of their choice, thus ensuring that their expectations are aligned with what the destination country has to offer. This has been highlighted in previous research [ 36 ], where, from the overall sample of 366 doctors, 55 respondents (24 %; 51 of whom had migrated passively) reported that they had received inaccurate information about the types of opportunities available to them in Ireland.…”
Section: Discussionmentioning
confidence: 90%
“…At present, there is a mismatch between what migrant doctors come to Ireland for, i.e. career progression and training, with what the Irish health system can offer in terms of postgraduate training and consultant posts [ 26 , 27 , 36 ]. Further research to compare the experiences of the two groups in our analysis (Irish-trained non-EU doctors and those trained outside Ireland) to those of Irish and EU nationals is warranted in order to fully examine the predictors of career progression in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficiary country was likely to be another high-income English-speaking country, as preferred by 70 % of foreign doctors who planned to migrate on from Ireland. These doctors could be considered to comprise variants of ‘career oriented migrant’ and ‘backpacker’ type migrants [ 17 , 18 ]. The findings in this paper show that onward migration, rather than returning home after having acquired training in another country, as has been previously proposed [ 19 ], may be the norm for some career-oriented migrants.…”
Section: Discussionmentioning
confidence: 99%